Spectroscopic Characterization of Co(II), Ni(II) and Cu(II) Complexes with Nitrogen and Oxygen Containing Schiff Base Derived from 3-Amino-2-methylquinazoline-4(3H)-one - Rai, B.K.; Thakur, Amrita; Divya (Asian Journal of Chemistry, 2012)
A bidentate nitrogen/ oxygen containing Schiff base ligand, 3-amino-2-methyl quinazoline-4(3H)hydrazone (AMQH) and its Co(II), Ni(II) and Cu(II) complexes have been synthesized and characterized by molar mass, elemental analyses, spectral (IR and electronic) molar conductivity measurements at the room temperature. On the basis of above spectral and physicochemical studies it is proposed that ligand 3-amino-2-methyl quinazoline-4(3H)hydrazone acts in a bidentate manner and coordination proposes through amino group of quinazoline and azomethine N atom. The remaining coordination of metal ions are satisfied by negative ions such as Cl–, Br–, I– and NO3–. The electronic spectral data proposes an octahedral geometry for Ni(II) and Co(II) while the geometry of Cu(II) complexes are proposed to be distorted octahedral in nature.